Loving Ebola-chan: Internet memes in an epidemic. (April 2017) - Marcus, Olivia Rose; Singer, Merrill
In this article, the authors provide a layered analysis of Ebola-chan, a visual cultural artifact of the 2014–2015 Ebola outbreak. Rather than considering her as a two-dimensional anime character (i.e. as a simple iconic coping mechanism and/or a fear response), this recent Internet meme is analyzed using an integrated semiotic and structural approach that involves discussion of the genesis of disaster humor in light of the changing world of the Internet, the history of anthropomorphism of disease, and the biosocial nature of an infectious disease epidemic. Our analysis is designed to advance both the anthropology of the Internet and the anthropology of infectious disease. As a multi-vocal symbol with different meanings for different audiences, Ebola-chan represents a social response to a lethal epidemic in the digital age.